A Study on Factors Affecting Investment Decisions among Individuals - Bhandari, Pratham; Nunes, Natasha D (International Journal of Engineering and Management Research, 2025)
This study examines the preferred investment options and key factors influencing investment decisions among individuals in Vapi region, utilizing primary data collected through questionnaires alongside secondary data from established sources. Drawing from literature that identifies demographic, economic, psychological, social, and organizational elements, alongside behavioral biases and external factors, this research analyzes investor choices. Primary data insights collected from the questionnaires, complementing existing models like KANO and AHP, reveal that potential return, risk level, market conditions, tax implications, and company reputation are significant drivers of investment decisions. Investment decisions are critical financial choices that involve allocating resources to various assets or projects to achieve financial objectives, highlight variations across demographic segments, enriching our understanding of investor behavior in Vapi region and providing valuable insights for financial stakeholders.